PF.11 Abnormal Platelet Function is Seen in Women with Unexplained Recurrent Miscarriage During Pregnancy. (26th April 2013) - Dempsey, M; Flood, K; Burke, N; Murray, A; Mullers, S; Fay, L; Cotter, B; Fletcher, P; Geary, M; Kenny, D; Malone, FD
Abstract : Objective: To evaluate platelet aggregation in patients with a history of recurrent miscarriage (RM) during a subsequent successful pregnancy and compare them to healthy pregnant controls. Study design: A prospective longitudinal study was performed to compare platelet function in 30 patients with a history of three consecutive unexplained first trimester pregnancy losses and 30 healthy age-matched pregnant controls. Exclusion criteria included the use of anti-platelet medications such as aspirin and medical conditions that can affect platelet function. Light transmission aggregometry was used to assay platelet agonists at different times and concentrations to create dose-response curves. Results: In contrast, to the increased platelet aggregation response seen in healthy controls, platelet reactivity in patients with RM peaked at 12–14 weeks gestation, highlighted by the increased aggregation response to epinephrine (p = 0.0008) and collagen (p < 0.0001) and then decreased in the third trimester in response to epinephrine (p < 0.0001), arachidonic acid (p < 0.0001) and Thrombin Receptor Activating Peptide (p < 0.0001). Conclusion: Patients with a history of recurrent miscarriage have significantly different platelet function when compared to healthy controls, in particular during the first trimester. Knowledge of which patients have impaired platelet function may allow for more targeted therapy in the setting of recurrent miscarriage.